A new species of Protozantaena Perkins, 1997 from the Great Escarpment of South Africa (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2022)
Protozantaena birdi sp. nov. is described, based on specimens collected from the Compassberg and Winterberg ranges in the Eastern Cape Great Escarpment, South Africa; the seventh known species of the genus. Morphologically, the new species appears closely related to P. labrata Perkins, 1997, described from the Naukluft Range in the Central Namibian Great Escarpment. Both species live in the margins of small streams in open, semi-arid landscapes.